About women’s concerns in a humorous way in the pages of the magazine “Mucha” - Milewska, Marta (Laughter, humour, satire, 2024)
One of the satirical and humorous magazines in the Kingdom of Poland was “Mucha”. The editors of “Mucha” carefully observed the fair sex, and then transferred their observations to the pages of the magazine. Women’s worries about education, finding a suitable candidate for a husband, marriage, raising children, etc. became the subject of satire. The editors of “Mucha” showed the above-mentioned women’s concerns in a distorting mirror, while criticizing women’s vanity. In the texts published in the “Mucha” magazine, women’s ills regarding various aspects of their lives were aptly hidden.